Application of the Self-Potential Method to Know the Distribution and Direction of Leachate Flow in the Alak Final Processing Site (TPA) Area, Kupang City - Yanti Boimau; Wenti Marlensi Maubana (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
The research using the Self-potential method has been carried out at the Final Processing Site (TPA) area of Alak District, Kupang City, East Nusa Tenggara. The purpose of this study is to determine the direction of leachate waste flow and distribution. Data acquisition in this study used a closed-loop system in the process of collecting potential data. This closed-loop system means that potential data collection starts at one point and will end at that point. There are 3 loop paths with a distance of 10m between the porous spot electrodes. Based on the potential distribution value of the isopotential map, the lowest potential value is -35 mV, and the highest value is 40 mV, therefore, this study area can be assumed that the leachate flow direction is from the southeast to the southwest. This case is supported by the influence of the topographical effects where the subsurface fluid flows from a high place to a low place. Based on the results of this study, the leachate flow direction and distribution can provide information for mapping high-risk areas of contamination at the Final Processing Site (TPA) in Alak, Kupang City, East Nusa Tenggara.